2019
DOI: 10.3390/pr7120870
|View full text |Cite
|
Sign up to set email alerts
|

Using Real-Time Electricity Prices to Leverage Electrical Energy Storage and Flexible Loads in a Smart Grid Environment Utilizing Machine Learning Techniques

Abstract: With exposure to real-time market pricing structures, consumers would be incentivized to invest in electrical energy storage systems and smart predictive automation of their home energy systems. Smart home automation through optimizing HVAC (heating, ventilation, and air conditioning) temperature set points, along with distributed energy storage, could be utilized in the process of optimizing the operation of the electric grid. Using electricity prices as decision variables to leverage electrical energy storag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…In this study, we compared the performance and applicability of two RL algorithms-ANN-PSO and PPO-by exploring their methods and applying them on stochastic steady-state economic optimization of a CSTR with FP-NLP as a benchmark algorithm [4][5][6]. We evaluate the RL algorithms' performance with their profitability and online computational times, and their applicability with their data requirements and training efficiencies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we compared the performance and applicability of two RL algorithms-ANN-PSO and PPO-by exploring their methods and applying them on stochastic steady-state economic optimization of a CSTR with FP-NLP as a benchmark algorithm [4][5][6]. We evaluate the RL algorithms' performance with their profitability and online computational times, and their applicability with their data requirements and training efficiencies.…”
Section: Discussionmentioning
confidence: 99%
“…Many chemical processes, like coal combustion and bioreactors, are complex, and thus deriving appropriate models and optimizing outputs is difficult [1][2][3]. Machine learning has shown success in optimizing complex systems such as scheduling electricity prices to manage demand and maximize power grid performance [4][5][6]. This motivates exploration of other machine learning techniques like reinforcement learning (RL) on model-free optimization [7].…”
Section: Motivationmentioning
confidence: 99%
“…Knowledge of these quantities is often limited to historic values, and for this reason, ML based forecasting techniques are often proposed in the literature. In [26] authors propose a proactive prediction of the energy demand of an entire city to be included in an intelligent management system for energy storage and flexible loads. Forecasting through deep learning techniques are also promising with good results for long-short-term-memory (LSTM) networks [27][28][29] and recurrent LSTM [27].…”
Section: Machine Learning For Battery Energy Storage Systemsmentioning
confidence: 99%
“…Although there may be a substantial benefit for homeowners to change their energy behavior, the use of market signals at the grid level can also be a way to turn residential buildings into a grid asset. On a similar topic, Sheha et al have demonstrated that a realtime market can be an effective means for coordinating demand-side behavior, allowing the grid to leverage distributed energy resources such as battery storage and home energy management systems [20,21].…”
Section: Grid and Micro-grid Applicationsmentioning
confidence: 99%